Intelligent control systems in eco-marketing for green construction - Gulsara Ostonakulova; Sitora Sayfitdin Qizi Odilova (BIO Web of Conferences)
This study explores how the presence of smart control systems manifests itself in stakeholders’ perceptions of their role and impact in the context of eco-marketing for green construction. The rise of digital automation and intelligent control technologies has enabled new forms of sustainable building management, but the nature of these technological advancements, particularly the decision-making processes in shaping eco-marketing strategies, is not well understood. This research aims to examine the task of integrating smart control systems into green construction marketing based on data deriving from a cross-sectional dataset, for instance, market trends, stakeholder preferences, and other technological developments, with the development of a relevant model for assessing and prioritizing adoption factors. We employ the Analytic Hierarchy Process (AHP) method to analyze empirical data conducted with construction firms, policymakers, and industry experts, and we identify six key mechanisms of successful eco-marketing implementation, namely resource efficiency, regulatory compliance, consumer engagement, cost-effectiveness, technological adaptability, and environmental impact. Our results illustrate that from a stakeholder’s perspective, the integration of smart control systems in eco-marketing for green construction is a key positive element of sustainability-driven business models. The study furthers understanding of the implications of technological advancements and stakeholder engagement on eco-marketing efficiency and green construction adoption. In this paper, a methodological and instrumental solution to the current problem of creating the most effective intelligent control-based eco-marketing framework in a sustainable construction ecosystem is proposed.